A case study of strategies for fostering international, interdisciplinary research - Halvorsen, Kathleen E. (2016)
Bringing together and successfully managing a highly interdisciplinary (ID) research team of socioeconomic, biophysical, and engineering scientists is highly challenging, particularly when that team includes 20 scientists and students across six countries. This paper reports on the results of evaluating the success of such a team as it studies the socioecological impacts of bioenergy development across the Americas. We find that the team has succeeded according to several different metrics. We demonstrate that the literature on accelerated sustainability transitions and small group team creation, development, and management holds valuable lessons for the success of ID teams.